Twórca - stereotyp - profilowanie, czyli literacka rzeczywistość alternatywna - Tokarz, Bożena (Przestrzenie Teorii, 2007)
The man lives in the culture built by him, which also includes stereotypes both created and used by the writer, belonging to the structure of the composition the stereotypes reference convention, scheme, model and cliché. They are forms of consciousness and as such they do not make a category in poetics, becoming closer to the rhetoric embodied by different shapes of thoughts. At the same time they are not shapes of thoughts, but rather forms of consciousness. Stereotypes are terms and phenomena on the border of humanities, such as myth or topos. They exist in the area of all culture. The community sanctions their presence, both positive and negative.